Volume 2: Reliability, Availability and Maintainability (RAM); Plant Systems, Structures, Components and Materials Issues; Simp 2013
DOI: 10.1115/power2013-98075
|View full text |Cite
|
Sign up to set email alerts
|

Air Cooled Two-Stage Rankine Cycles for Large Power Plants Operating With Different Working Fluids: Performance, Size and Cost

Abstract: A two stage Rankine cycle for power generation is presented in this paper. It is made of a water steam Rankine cycle and an Organic Rankine bottoming Cycle. By using an organic working fluid with higher density than water, it is possible to reduce the installation size and to use an air-cooled condenser. Following our previous studies, 3 high critical temperature organic fluids, R245fa, R365mfc, isopentane (iC5) and ammonia are tested as potential candidates for this application. The performances of the two st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Compared with the traditional steam Rankine cycle, organic fluids used in ORCs with high critical temperature, low triple point temperature, and low condensation temperature contribute notably to the recovery of heat from low temperature sources in terms of system performance [8].…”
Section: Chemical Propertymentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with the traditional steam Rankine cycle, organic fluids used in ORCs with high critical temperature, low triple point temperature, and low condensation temperature contribute notably to the recovery of heat from low temperature sources in terms of system performance [8].…”
Section: Chemical Propertymentioning
confidence: 99%
“…Critical temperature is considered as the primary criteria to select the working fluids by most studies. Liu et al [8] indicated that the critical temperature should be as high as possible compared with the evaporation temperature in the application of a two-stage Rankine cycle in terms of ORC efficiency.…”
Section: Critical Temperaturementioning
confidence: 99%
See 1 more Smart Citation